The medie power of comunication - Camba Pérez, Julio Álvaro (Revista Universidad de Guayaquil, 2011)
There are two main schools of thought in social communication sciences: The research and analysis of the dominant mass media in our country, U.S. current positivist empirical, practical to service commercial and ideological purposes of communication, and the European mainstream and critical, which is concerned primarily to determine the underlying issues explicit and communication processes, ie, the ideological aspects where the communication system should be framed, is a sociopolitical position that attempts to explain the set of global interrelationships in which the mass media play an important role in the slave society in other scientific disciplines such as linguistics, psychology, sociology, semiology, anthropology among others. This work seeks to discriminate communication trends that are broadcast on national television stations, are systematized processes of television production in television news, trying to prove that paradigm that consists in the operating style of the American media that used in our country, apply from the concept of pragmatic communication, identifying communication flows and decisions to publish and treatment of the events which becomes managed from a book published as a truth published.